JODHANGAN - Siti Munawaroh (Balai Pelestarian Nilai budaya Daerah Istimewa Yogyakarta, 2019)
This research is about the Jodhangan practice which is a tradition of agrarian society found in Selopamioro Imogiri village, under Bantul Regency. The research questions are why the Jodangan practice is performed in Cerme Cave and what values that are comprised of in the Jodhangan tradition. This qualitative research collected the data from library research and interviews. The results of the study show that the Jodhangan tradition is once in a year on Sunday Pahing in Besar (Dzulhijjah) month according to the Javanese (Islamic) calendar. This tradition is an expression of gratitude to God Who has rendered good harvests, prosperity, and welfare to the people. Cerme Cave is selected as the place to perform the Jodhangan practice because it is believed to be a sacred place inherited by the Wali Sanga (the Nine Islamic Saints). The Jodhangan tradition comprises religious values, mutual help, solidarity, deliberation, and social values. The continuation of the Jodhangan tradition is expected that it can be used to promote solidarity or tolerance among fellow citizens, so that they would be easily mobilized for more positive activities.